Environmental Accounting Analysis of the Increase of Raw Materials in the Government Sector - Muhammad Aras Prabowo; Kurnia Syafa Salsabila; Sintia Nur Afifah (Trescode Green Organization, 2025)
The main objective of this study is to examine how rising raw material costs hinder government efforts to achieve sustainable development and protect the environment point to help governments assess and manage responsibly the impact of rising raw material costs point this article examines the importance of environmental accounting as a strategic basis for this research using the Systematic Literature Review (SRL) methodology. Using information presented from relevant journals between 2013 and 2024, the SLR technique was used to identify platforms and approaches to information system development in Indonesia. And the SLR method for determining, examining, assessing and interpreting all the currently available literature on how environmental accounting helps the government sector manage the impact of rising raw material prices on environmental sustainability in light of related and interesting questions. The phenomenon of systematic review and journal identification can be completed using the SLR technique with each stage of the process in accordance with predetermined guidelines. The findings of this study show that environmental accounting is a method for determining, evaluating and recording the advantages and disadvantages of various government initiatives towards the environment. Successful policies and measures to reduce the adverse impact on the environment due to rising raw material costs require prompt consideration of this information. The main objective of this study is to examine how rising raw material costs hinder government efforts to achieve sustainable development and protect the environment point to help governments assess and manage responsibly the impact of rising raw material costs point this article examines the importance of environmental accounting as a strategic basis for this research using the Systematic Literature Review (SRL) methodology. Using information presented from relevant journals between 2013 and 2024, the SLR technique was used to identify platforms and approaches to information system development in Indonesia. And the SLR method for determining, examining, assessing and interpreting all the currently available literature on how environmental accounting helps the government sector manage the impact of rising raw material prices on environmental sustainability in light of related and interesting questions. The phenomenon of systematic review and journal identification can be completed using the SLR technique with each stage of the process in accordance with predetermined guidelines. The findings of this study show that environmental accounting is a method for determining, evaluating and recording the advantages and disadvantages of various government initiatives towards the environment. Successful policies and measures to reduce the adverse impact on the environment due to rising raw material costs require prompt consideration of this information.